Pengaruh Latihan IckySshuffle Ladder Terhadap Kelincahan Dalam Olahraga Bulutangkis - Bangkit Anugrah; Risma Risma; Hendra Rustiawan; Isna Daniyati Nursasih (Jurnal Keolahragaan, 2023)
This study aims to determine the effect of Icky Shuffle Ladder training on agility in badminton. Agility is an important component in badminton that supports athletes' performance in moving quickly and accurately. The research method used was an experiment with a One-Group Pretest-Posttest Design. The subjects of this study were 22 participants from the badminton extracurricular club at SMAN 1 Parigi, selected using total sampling technique. The instrument used to measure agility was the Illinois Agility Run Test, which is standardized and widely used in measuring athletic performance. The research results showed a significant increase between pretest and posttest scores after the Icky Shuffle Ladder training intervention. This was proven by statistical analysis showing a significant difference (p < 0.05). These findings indicate that the Icky Shuffle Ladder exercise is effective in improving the agility of badminton athletes. Therefore, this exercise is recommended as part of a physical training program to enhance performance in badminton.